Latin American humpback whales song dynamics - Djokic, Divna (2021)
Male humpback whales are known for their intricate singing. The changes of these songs can be gradual, called evolution, or rapid — revolutions. Despite this versatility, all males from the same breeding ground adopt the same type of the song during a given breeding period. The rules that determine these changes are not well known. A possible mechanism for generating such changes in singing may be the interchange of song components in the feeding area, where distinct stocks can meet, and potentially interact. Another possibility could be the visit of an individual from another stock during the breeding season. A third potential option would be a unidirectional song drift (so far observed in Oceania, where a single song type travels from one population to another in subsequent years). Despite having limited data on the level of interaction of distinct stocks from the two oceans of Latin America, from genetic analysis and photo identification, I hypothesize that this type of contact is detectable through the type and composition of the songs. To determine which of these aforementioned mechanisms best explains song change in distinct stock of humpback whales in Latin America, I assembled a database of 1718 minutes of recordings over 4 consecutive breeding seasons (2016-2019) in 8 different locations in breeding areas in Central and South America. The methodology applied in this work is divided into new methods, built for this study (a key for classification of song units and matrices for visualization of recurrent patterns in humpback whale song, based on the Levenshtein distance), existing methods, previously not applied in this area of research (Jaccard similarity index used to compare differences between song unit repertoires) and well-established methods applied in humpback whale song research (Levenshtein's similarity index and complexity scores for song units). Even though not all the results obtained by our research are in agreement with the contemporary literature, all our methods agree on the conclusion that the stocks of humpback whales in Latin America, explored in this study, maintain acoustic contact, which is variable in intensity and type, and that this contact (from these or other stocks) is probably a determining factor for the never-ending changes we see in humpback whale songs.